Comparison of the stabilized waste soil properties and stabilization mechanism of phosphogypsum-fly ash-steel slag based cement versus Portland cement - Jianmin Guo; Xizhong Xu; Xiaohui Song; Jincheng Wei; Wencheng Shi; Yu Xia (PLoS ONE, 2025)
Through physical and chemical reactions in the presence of phosphogypsum, steel slag and fly ash modify the load-bearing skeleton and fill the pores of the wasted soil, resulting in high-strength performance. Extensive experiments that compared Portland cement with phosphogypsum-fly ash-steel slag-based cement (PFS cement) revealed that the later-stage unconfined compressive strength (UCS) of PFS cement exceeded that of Portland cement by approximately 33.18%. In terms of the stress-strain curve, the maximum stress and yield strength of PFS cement-stabilized waste soil were 40% to 50% higher than those of Portland cement. In the dry-wet cycle resistance experiment, PFS cement-stabilized waste soil showed a compressive strength increase of 15.17% over Portland cement. Furthermore, during the freeze-thaw cycle test, PFS cement-stabilized waste soil demonstrated a 29.95% higher performance compared to Portland cement. When used as a solidifying agent, PFS cement exhibits significant advantages over Portland cement in backfilling for underground engineering, trenches, roadbeds, bridge abutments, and road base layers.